Genome-wide identification of MGT gene family in soybean (Glycine max) and their expression analyses under magnesium stress conditions - Ammar Anwar; Junaid Akhtar; Saba Aleem; Maida Aleem; Muhammad Khuram Razzaq; Saud Alamri; Qasim Raza; Iram Sharif; Arooj Iftikhar; Shehreen Naseer; Zaheer Ahmed; Iqrar Ahmed Rana; et al. (BMC Plant Biology)
Abstract Background Magnesium (Mg) is essential for plant growth and development and plays critical roles in physiological and biochemical processes. Mg deficiency adversely affects growth of plants by limiting shoot and root development, disturbing the structure and membranes of the grana, reducing photosynthesis efficiency, and lowering net CO2 assimilation. The MGT (Magnesium transporter) family is responsible for the absorption and transportation of magnesium in plants. Although the MGT family has been identified in different plant species, research regarding the soybean MGT genes is limited. Results In the current study, a total of 39 MGT genes distributed on 17 different chromosomes were identified in soybean. Phylogenetic analysis classified GmMGTs into three subgroups, NIPA, MRS2/MGT, and CorA, which showed little homology with MGTs of Arabidopsis thaliana and Oryza sativa members and clustered tightly with GmMGTs. Gene structure and conserved motif analysis also confirmed similar grouping in GmMGTs. The expansion of the GmMGT members in NIPA and MRS2/MGT was predicted, while CorA was identified as the most conserved group in G. max. Segmental duplication under purifying selection pressure was identified as the major driving force in the expansion of MGTs in soybean. GmMGTs showed diverse tissue-specific and stress-response expression patterns due to the presence of stress-related cis-regulatory elements in their promoter regions. Under Mg-deficiency and surplus stress conditions, a decrease in root length, shoot length, and root and shoot fresh as well dry weight in susceptible genotypes showed the variegated expression of MGTs in soybean genotypes. Furthermore, the upregulation of GmMGT2 and GmMGT29 in tolerant genotypes in response to Mg-deficiency as well as surplus stress conditions in leaves suggested the essential role of GmMGT genes in the absorption and transportation of Mg in soybean leaves. Conclusion This study presents a comprehensive analysis of the MGT gene family in soybean, providing insights into their evolutionary relationships, gene classification, protein structures, and expression patterns under both Mg deficiency and Mg surplus conditions.